CaO stabilized ZrO2 coating intended to reduce corrosion on steel and aluminum substrates (Superficies y Vacío, 2017)
In this work, we studied the anticorrosive properties of sol-gel nanostructured calcium stabilized zirconia coatings, deposited onto 304 stainless steel and commercial aluminum substrates by dip-coating and spin-coating. During the ceramic oxide synthesis, zirconium oxychloride octahydrate was used as precursor and calcium acetate monohydrate was used as stabilizer of the cubic zirconia structure, in a precursor/stabilizer molar ratio of 0.84/0.16. The gel films deposited on steel and aluminum were heat treated at 550 y 600 °C during 5 and 10 min, respectively, and the adherence of the resulting ceramic films was evaluated. Continuous coatings were obtained that reached average thicknesses between 2 y 3 mm when deposited on stainless steel, and between 1.5 y 1.6 on aluminum, depending on the coating method. The corrosion resistance of the best-adhered coatings was evaluated during 500 h in a saline chamber, according to ASTM B117-11. All the substrate-coating combinations showed a very good corrosion resistance. For the two substrate types, the films deposited by dip-coating showed higher corrosion resistance than the ones deposited by spin-coating. The anticorrosive protective effect of the coatings was better for the aluminum substrates, compared to the stainless-steel substrates.